Analsis Liquiditas, Struktur Modal Dan Profitabilitas Terhadap Nilai Perusahaan Manufaktur di Indonesia - Arie Setyo Dwi Purnomo (Eco-Entrepreneur, 2022)
The purpose of this research is to know the existence of Capital Structure (LDER), Profitability (ROE), and Likuidity (CR) partially at Automotive Company listed in Indonesia Stock Change (BEI) period 2015-2019.“The date used in this secondary date, namely the financial purposive sampling method which produces 13 componies. For testing instruments using classic assumption test, while date analysis techniques used to determine the hypothesis using multiple linera regression using t test.Based on the results of the t test indicate that Capital Structure (LDER) have negative significant influence to Firm Value (PBV), Profitability (ROE) have negative not significant to Firm Value (PBV), and LIkuidity (CR) have negative not significant to Firm Value (PBV).The results of this study are only limited to the automotive manufacturing sector. So that the information contained in this study cannot be generalized to objects such as banking, where the liquidity factor is strictly guarded by central bank regulations. So that further research can explore different objects related to different industrial sectors